Among wolves ethnography and the immersive study of power - Pachirat, Timothy 1976- (Routledge series on interpretive methods, 2018)
"Summoned by an anonymous Prosecutor, ten contemporary ethnographers gather in an aging barn to hold a trial of Alice Goffman's controversial ethnography, On the Run. But before the trial can get underway, a one-eyed wolfdog arrives with a mysterious liquid potion capable of rendering the ethnographers invisible in their fieldsites. Presented as a play that unfolds in seven acts, the ensuing drama provides readers with both a practical guide for how to conduct immersive participantobservation research and a sophisticated theoretical engagement with the relationship between ethnography as a research method and the operation of power. By interpolating "how-to" aspects of ethnographic research with deeper questions about ethnography's relationship to power, this book presents a compelling introduction for those new to ethnography and rich theoretical insights for more seasoned ethnographic practitioners from across the social sciences. Just as ethnography as a research method depends crucially on serendipity, surprise, and an openness to ambiguity, the book's dramatic and dialogic format encourages novices and experts alike to approach the study of power in ways that resist linear programs and dogmatic prescriptions. The result is a playful yet provocative invitation to rekindle those foundational senses of wonder and generative uncertainty that are all too often excluded from conversations about the methodologies and methods we bring to the study of the social world."--Provided by publisher.